A Laboratory Forced-Oscillation Apparatus for Measurements of Elastic and Anelastic Properties of Rocks at Seismic Frequencies - Mikhaltsevitch, Vassily; Lebedev, Maxim; Chavez, Rafael; Vargas, Euripedes A.; Vasquez, Guilherme F. (Frontiers in Earth Science, 2021)
In presented paper, we describe the technical and physical aspects of the application of a low-frequency apparatus based on a longitudinal type of forced oscillations. In particular, we investigate the influence of the strain gauge position on a tested sample on measurement results, we also examine the creep effect associated with the mineralogy of rocks, as well as the dispersion and attenuation in a liquid-saturated rock sample caused by the presence of the volume of pore fluid exterior to the sample (dead volume). The effect of the position of the strain gauges is investigated using a cylindrical acrylic sample and two pairs of strain gauges fixed in the middle and at one of the sample ends under a uniaxial pressure of 15 MPa. The obtained results demonstrate that elastic and anelastic parameters of the tested sample are independent from the location of the strain gauges. The impact of the creep phenomenon on elastic moduli was studied using three room-dry samples of Savonnieres limestone, Berea sandstone and Eagle Ford shale. The measurements were conducted for 120 hours at a frequency of 2 Hz under a uniaxial pressure of 10 MPa and demonstrated that the low-frequency moduli of all rocks were noticeably reduced with time. The effect of dead volume was investigated at seismic frequencies using limestone saturated with n-decane. It was found that the Young’s and bulk moduli exhibit strong dispersion at frequencies above 10 Hz if the dead volume is close to or greater than the pore volume of the sample. We also found that the characteristic frequency of dispersion corresponding to the attenuation peak is independent of the size of the dead volume and determined only by the physical parameters of the sample and pore fluid. We present also the results of the Young’s modulus and attenuation measurements conducted at seismic frequencies on vertical and horizontal shale samples saturated with water. It was shown that the relationship between the extensional attenuation and the Young’s modulus dispersion observed in the samples saturated at a relative humidity of 97.5% is consistent with the Kramers-Kronig relation.